Identity issues in European literatures - Adamowicz-Pośpiech, Agnieszka 1971-; Dampc-Jarosz, Renata; Warmuzińska-Rogóż, Joanna (Andersheit - Fremdheit - Ungleichheit, 2021)
This trilingual volume sets out to address the forms of otherness and types of the Other through the example of case studies of European literatures and to look at them from an intercultural perspective. The concept of the Other not only varied from epoch to epoch, but it was tied to the development of the respective culture. Reflection on identity and otherness forms the core of the contributions collected in this volume, which focus on texts, authors or myths from French, German, English, Polish, Russian and Swedish literature from the 16th century until today. The selection of texts is intended to demonstrate the complexity and originality of the theme of otherness versus identity in contemporary literary research and to point to ist topicality. The volume sees itself as the result of comparative studies in which literary researchers discuss selected aspects of identityforming otherness, especially on a narrative level